University Students' Perceptions of Kahoot as a Tool for Structure and Writing Practice in TOEFL Preparation in Indonesia - Ahyadi; Ikhsan; Ridwan (IJLHE: International Journal of Language, Humanities, and Education, 2024)
This study investigates students' perceptions of Kahoot as a gamified assessment tool for TOEFL Structure and Written Expression. Utilizing a quantitative approach, the study analyzes responses from 19 participants who engaged in Kahoot-based evaluations. Findings reveal that Kahoot's interactive features—leaderboards, real-time feedback, and competitive scoring—significantly enhanced students' motivation, engagement, and enthusiasm during the evaluation process. The majority of participants expressed strong interest in using Kahoot for future evaluations and incorporating it into their teaching practices, citing its user-friendliness and effectiveness in sustaining attention throughout the assessment. Notably, no participants reported disinterest or demotivation, further reinforcing the platform’s potential as an engaging learning tool. This study highlights the transformative potential of gamified tools like Kahoot in creating dynamic learning environments that enhance traditional assessments. The results offer valuable insights for educators and curriculum developers seeking to integrate gamification into educational practices, particularly in high-stakes test preparation contexts. The implications of this research suggest that incorporating gamified tools can not only increase student engagement but also foster deeper learning through interactive and enjoyable assessment experiences. Moreover, such tools can bridge the gap between learning and assessment by making evaluations less intimidating and more accessible. Future research should explore its application across diverse educational settings and its long-term impact on learning outcomes